Detection of Toxoplasma gondii Infections using Virus-Like Particles Displaying T. gondii ROP4 Antigen - Kim, Min-Ju; Mao, Jie; Kang, Hae-Ji; Chu, Ki-Back; Quan, Fu-Shi (Korean journal of parasitology, 2021)
Toxoplasma gondii ME49 infections are typically diagnosed by serological tests. However, serological diagnosis of RH strain-induced toxoplasmosis remains unknown. In order to develop seradiagnosis of above 2 kinds of infections, we generated recombinant virus-like particles (VLPs) displaying the T. gondii rhoptry protein 4 (ROP4) and evaluated their potential in T. gondii ME49 or RH strain infection diagnostics. Mice were orally infected with either the tachyzoites of T. gondii (RH) or cysts of T. gondii (ME49) at various dosages, and sera were collected at regular intervals. ELISA-based serological tests were performed to assess IgG, IgM, and IgA antibody responses against ROP4 VLP antigen and tissue lysate antigen (TLA). Compared to TLA, IgG, IgM, and IgA levels to ROP4 VLP antigen were significantly higher in the sera of T. gondii RH-infected mice 1 and 2 week post-infection (PI). T. gondii-specific IgG antibody was detected at 1, 2, 4, and 8 week PI in the T. gondii ME49-infected mice with infection dose-dependent manner. These results indicated that the ROP4 VLP antigen was highly sensitive antigens detecting T. gondii RH and ME49 antibodies at an early stage.